1970
DOI: 10.1002/bjs.1800570809
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia on the platelet count

Abstract: The occurrence of low arterial oxygen tensions in postoperative patients is well established. The effect of hypoxia on platelets was therefore studied in 36 rabbits. Two groups were exposed to low oxygen mixtures and a third group was exposed to air in an environmental chamber. In all groups the period of exposure was 24 hours. The hypoxic rabbits showed increased platelet counts from the first to nineteenth days after exposure. The difference in counts between both hypoxic groups and the control rabbits was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Arterial venous thrombosis is observed under some cases of acute hypobaric hypoxia wherein activation of platelets has been observed during hypoxia exposure in human and animal studies [36][37][38]. Identification of membrane glycoproteins like GP9, GP6, GP4 and integrin subunits like ITGA2B, ITGB3 has been reported in study in which volunteers exposed to continuous hypobaric hypoxia.…”
Section: Plos Onementioning
confidence: 97%
“…Arterial venous thrombosis is observed under some cases of acute hypobaric hypoxia wherein activation of platelets has been observed during hypoxia exposure in human and animal studies [36][37][38]. Identification of membrane glycoproteins like GP9, GP6, GP4 and integrin subunits like ITGA2B, ITGB3 has been reported in study in which volunteers exposed to continuous hypobaric hypoxia.…”
Section: Plos Onementioning
confidence: 97%
“…In experimentallyinduced hypoxia, 3 weeks of intermittent asphyxia in rats, mimicking the intermittent asphyxia of human sleep apnoea, has no effect on platelet number but increases platelet aggregation [79]. There is good evidence that either hypobaric or normobaric continuous hypoxia causes thrombocytosis in the short-term (perhaps several hours to several days) but causes thrombocytopaenia in the longterm (perhaps several weeks) in rats [51,80,81], mice [82][83][84][85][86][87] and rabbits [88] although one study in rats reported long-term thrombocytosis [89]. The short-term thrombocytosis is observable when measured as early as one day after exposure to hypoxia [80,82,84,88] but the time course of changes in count during the first 24 hours, which would be more relevant to air travel, do not appear to have been measured in animal studies.…”
Section: Hypoxia and Platelet Number And Functionmentioning
confidence: 99%
“…There is good evidence that either hypobaric or normobaric continuous hypoxia causes thrombocytosis in the short-term (perhaps several hours to several days) but causes thrombocytopaenia in the longterm (perhaps several weeks) in rats [51,80,81], mice [82][83][84][85][86][87] and rabbits [88] although one study in rats reported long-term thrombocytosis [89]. The short-term thrombocytosis is observable when measured as early as one day after exposure to hypoxia [80,82,84,88] but the time course of changes in count during the first 24 hours, which would be more relevant to air travel, do not appear to have been measured in animal studies. In humans, breathing 13% oxygen for one hour had no effect on platelet count or volume [90] but breathing 12.8% oxygen for three hours, equivalent to exposure to an altitude of 12,000 feet (3,660 meters) caused an increase in platelet count [53].…”
Section: Hypoxia and Platelet Number And Functionmentioning
confidence: 99%
“…Die Untersehiede in den Thromboeytenzahlen zwisehen 1. Sowohl tierexperimentell als auch bei pulmonalen Erkrankungen wurde fiber eine Zunahme der Thromboeyten mit Abnahme der arteriellen Sauerstoffspannung beriehte$ [4,14], so dal~ der Anstieg der Thrombocyten aueh als Folge der mater und unmittelbar naeh der Geburt bestehenden niedrigen ar~eriellen 02-Spannung gedeutet werden kann. So bleibt wenig Zweifel, dal~ reife und unreife Neugeborene w/~hrend der 2.…”
unclassified